The Effect Of Immersion Eggs Using Thyroxine Hormones With Different Doses On Egg Hatchabillity, Growth, and Survival Rate Of Sheat-Fish Larvae (Ompok rhadinurus Ng) - Srimenda Br Ginting; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study was conducted on September-October 2019 in fish hatchery and Breeding laboratory, fisheries and marine faculty of RiauUniversity, Pekanbaru. The aim of this study wasto determine the effect of different thyroxine hormone doses on hatching rate, growth and survival rate of sheat-fish (ompok rhadinurus Ng). This study used a factorial complete random match (CRD) with 4 treatments and 3 replications. Different doses used on this study were; P1 (0 mg/L), P2 (0.05 mg/L), P3 (0.10 mg/L) and P4 (0.15 mg/L). Immersion of sheat-fish eggs with thyroxin hormone for 24 hours with ± 250 of sheat-fish eggs (0.5 g) and incubated  in a jar. Sheat-fish larvae maintained for 30 days. The results showed that different thyroxine hormone doses affected (P < 0.05) to fertilization rate (92.06%), incubation (21 hours 36 minutes), hatching rate (91.71%), and survival rateof sheat-fish larvae (93.30%) But, didn’t affect to absolute length growth, absolute weight growth, and specific growth rate of sheat-fish larvae. The best doses thyroxine hormone to increase hatching rate, incubation time, and fertilization rate was 0,10 mg/L. Keywords: Sheat-fish, thyroxin hormone, fertilization rate, incubation time, hatching rate, absolute growth, survival rate